An intra-action review conducted by the CDC Foundation during COVID-19 to evaluate emergency response procedures. (May 2023) - Bednar, H.; McMillan, S.; Seidl, M.; Powell, R.; Sidibe, T.
Abstract: Objectives: During times of emergency response, the CDC Foundation leverages partnerships and relationships to better understand the situation and respond rapidly to save lives. As the COVID-19 pandemic began to unfold, an opportunity became clear to improve our work in emergency response through documentation of lessons learned and incorporating them into best practices. Study design: This was a mixed methods study. Methods: The CDC Foundation Response, Crisis and Preparedness Unit conducted an internal evaluation via an intra-action review to evaluate and rapidly improve emergency response activities to provide effective and efficient response-related program management. Results: The processes developed during the COVID-19 response to conduct timely and actionable reviews of the CDC Foundation's operations led to the identification of gaps in the work and management processes and to creation of subsequent actions to address these issues. Such solutions include surge hiring, establishing standard operating procedures for processes not yet documented, and creating tools and templates to streamline emergency response operations. Conclusions: The creation of manuals and handbooks, intra-action reviews, and impact sharing for emergency response projects led to actionable items meant to improve processes and procedures and the ability of the Response, Crisis and Preparedness Unit to quickly mobilize resources directed toward saving lives. These products are now open-source resources that can be used by other organizations to improve their own emergency response management systems.